Transport, stability and plasma control studies in the TJ-II stellarator. (29th July 2015) - Sánchez, J.; Alegre, D.; Alonso, A.; Alonso, J.; Alvarez, P.; Arévalo, J.; Ascasíbar, E.; Baciero, A.; Baiao, D.; Barcala, J.M.; Blanco, E.; Borchardt, M.; et al.
Abstract: The main TJ-II results since 2012 are presented in this overview. Impurity confinement is studied showing an isotopic dependence of impurity confinement time, asymmetries in parallel impurity flows in TJ-II ion-root plasmas and impurity density asymmetries within a flux surface. In addition, first observations of electrostatic potential variations within the same magnetic flux surface are presented. Evidence of the impact of three-dimensional magnetic structures on plasma confinement and L–H transitions is also presented. The leading role of the plasma turbulence is emphasized by the observed temporal ordering of the limit cycle oscillations at the L–I–H transition. Comparative studies between tokamaks and stellarators have provided direct experimental evidence for the importance of multi-scale physics to unravel the impact of the isotope effect on transport. Novel solutions for plasma facing components based on the recently installed Li-liquid limiters (LLLs) have been developed on TJ-II, showing the self-screening effect of evaporating liquid lithium, protecting plasma-facing components against heat loads, and tritium inventory control. Regarding plasma stability, magnetic well scan experiments show that traditional stability criteria, on which the optimization of stellarator configurations is based, may miss some stabilization mechanisms. Further effects of ECRH on Alfvénic instabilities are investigated, showing that moderate off-axis ECH power deposition modifies the continuous nature of the Alfvén eigenmodes, and frequency chirping sets in. This result shows that ECH can be a tool for AE control that might be ITER and reactor-relevant.